Local Cultural Values That Support and Inhibit West Sumba Regional Development - Rade Duka, Julitha Madeleine; Mediatati, Nani (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This research aims to analyze local cultural values that support and hinder regional development in West Sumba. West Sumba is a region rich in unique cultural heritage, but also faces challenges in development efforts. This research uses qualitative methods combined with case study methods. Data collection through in-depth interviews, participant observation, and document analysis. The research results show that strong cultural values such as mutual cooperation, togetherness and customs have an important role in supporting development in West Sumba. Gotong royong allows communities to work together on local development projects, while togetherness strengthens collaboration between government, communities and the private sector. However, some cultural values can also hinder development, such as a strong attachment to tradition which may hinder innovation, as well as norms that limit the role of women in the development process. This research contributes to the understanding of how cultural values can influence development efforts in areas with a rich cultural heritage. The practical implication of this research is the need for a balanced approach between utilizing positive cultural values and overcoming obstacles that may arise due to certain cultural values. By considering these complex dynamics, policy makers and decision makers can design more effective and sustainable development programs in West Sumba.